US healthcare costs attributable to type A and type B influenza. Issue 9 (2nd September 2017) - Yan, Songkai; Weycker, Derek; Sokolowski, Stefania
ABSTRACT: While the overall healthcare burden of seasonal influenza in the United States (US) has been well characterized, the proportion of influenza burden attributable to type A and type B illness warrants further elucidation. The aim of this study was to estimate numbers of healthcare encounters and healthcare costs attributable to influenza viral strains A and B in the US during the 2001/2002 – 2008/2009 seasons. Healthcare encounters and costs in the US during the 2001/2002 – 2008/2009 seasons for influenza type A and influenza type B were estimated separately and collectively, by season and age group, based on data from published literature and secondary sources for: rates of influenza-related encounters requiring formal healthcare, unit costs of influenza-related healthcare encounters, and estimates of population size. Across 8 seasons, projected annual numbers of influenza-related healthcare encounters ranged from 11.3–25.6 million, and healthcare costs, from 2.0–5.8 billion. While the majority of influenza illness was attributable to type A strains, type B strains accounted for 37% of healthcare costs across all seasons, and as much as 66% in a single season. The outpatient burden of type B disease was considerable among persons aged 18–64 y while the hospital cost burden was highest in young children. Influenza viral strain B was associated with considerable health system burden each year during the period of interest. Increasing influenza vaccine coverage, especially with the recently approved quadrivalent products including an additional type B strain, could potentially reduce overall annual influenza burden in the US.